PENGGUNAAN ALAT PERAGA PANRAM UNTUK MENINGKATKAN HASSIL BELAJAR MEMBACA DAN MENAFSIRKAN DATA MURID KELAS V UPTD SD NEGERI SIKUMANA 1 - Emiliana Nona Keban; Netty Elisabet Antoneta Nawa; Adam Bol Nifu Benu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve learning outcomes in reading and interpreting data using Panram teaching aids for fifth-grade students of UPTD SD Negeri Sikumana 1, Kupang City. The background of this study is based on the low learning outcomes of students, and the learning process is still centered on the teacher so that students are passive during learning. This study uses Classroom Action Research (CAR) which is carried out in two cycles consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 19 fifth-grade students of UPTD SD Negeri Sikumana 1, Kupang City. Data collection techniques were carried out through observation, learning outcome tests, and documentation. The results showed that the use of Panram teaching aids was able to improve teacher and student activities, as well as learning outcomes in reading and interpreting data. In cycle I, the average teacher activity was 77.5 and increased in cycle II to 97.5. While the average student activity in cycle I was 62.66 and increased in cycle II to 81.86. With the percentage of student learning outcomes in cycle I of 71.42% and increased to 85.71%. The comparison of learning outcome tests in cycles I and II was 14.29%. Therefore, it can be concluded that using Panram teaching aids for reading and interpreting data can improve student learning outcomes.